Fusion of Factor IX to Factor XIII-B Sub-Unit Improves the Pharmacokinetic Profile of Factor IX - Le Quellec, Sandra; Enjolras, Nathalie; Perot, Eloïse; Girard, Jonathan; Negrier, Claude; Dargaud, Yesim (Thrombosis and Haemostasis, 2018)
Prophylaxis is currently considered the optimal care for severe haemophilia. For patients and their families one of the major difficulties with prophylaxis is the need for frequent venipunctures. The half-life of standard factor IX (FIX) concentrates is approximately 18 hours, which requires 2 or 3 intravenous infusions per week to achieve bleeding prevention in patients with severe haemophilia B. Prolonging the half-life of FIX can therefore reduce the frequency of infusions. Recently, extended half-life recombinant FIX (rFIX) concentrates have been developed. We designed a new rFIX molecule fused to coagulation FXIII-B sub-unit. This sub-unit is responsible for the long half-life of the FXIII molecule (10–12 days). The rFIX-LXa-FXIIIB fusion protein contains a short linker sequence cleavable by activated FX (FXa), to separate rFIX from the carrier protein as soon as traces of FXa are generated, leaving rFIX free to perform its enzymatic role in the tenase complex. The rFIX-LXa-FXIIIB fusion protein was expressed in human hepatic Huh-7 cells and Chinese hamster ovary cells, and both wild-type rFIX (rFIX-WT) and rFIX-LXa-FXIIIB showed similar clotting activity and thrombin generation capacity in vivo after injection in haemophilia B mice compared with rFIX-WT. The half-life of the rFIX-LXa-FXIIIB molecule in WT mice and rats was 3.9- and 2.2-fold longer, respectively, compared with rFIX-WT. A potential advantage of this new molecule is its capacity to bind to fibrinogen via FXIII-B, which might accelerate fibrin clot formation and thus improve haemostatic capacity of the molecule.
Keywords: coagulation Factor IX; half-life extension; fusion protein; factor XIII-B sub-unit; haemophilia B